THE RECEPTION AND CRITICAL RECEPTION OF BYRON AND LERMONTOV'S POETRY IN THEIR RESPECTIVE COUNTRIES - Ruzibayeva Aziza Kahramanovna (Web of Journals Publishing, 2024)
This article examines the reception and critical reception of the poetry of Lord Byron in England and Mikhail Lermontov in Russia. Both poets were considered controversial figures in their respective countries, with their works often challenging societal norms and conventions. By analyzing the ways in which their poetry was received by contemporary audiences and critics, this study sheds light on how their works were perceived within the cultural contexts of England and Russia during the Romantic era.
Keywords: Lord Byron, Mikhail Lermontov, poetry, reception, critical reception, England, Russia, Romantic era.